Analisis Biaya dan Waktu Menggunakan Crashing Method pada Proyek Peningkatan Jalan Banyakan – Tiron Kediri - Mahendra, Muhammad Yusuf; Oetomo, Wateno (Portal: Jurnal Teknik Sipil, 2023)
In the world of construction, time, quality, and cost are three important components in a construction project planning. Therefore, in a construction project, project control is needed. The wide scope of project work is a driving factor that project work can experience a time delay problem. Project delays can be anticipated by accelerating (crashing) which in its implementation must still pay attention to cost factors. Crashing is a deliberate, systematic and analytical process by testing all activities in a project centered on activities that are on the critical path. Accelerating the time of each activity definitely causes the project completion time to be faster. But the acceleration of the time of these activities will also affect the project in terms of cost. This research was conducted on the Banyakan - Tiron Kediri Road Improvement Project, where the achievement of field progress in week 11, the project experienced a delay of 16.90% with a progress value of 14.72% of the planned progress of 31.62%. This research was conducted with alternatives to increase working hours (overtime) and increase the number of workers. The acceleration results of the two alternatives are compared and the most optimal acceleration alternative is sought. The results of the analysis of the acceleration with the crashing method with alternative additional working hours obtained the total duration of the project to 112 days, from the total duration of the normal condition project for 135 days. Then there was a change in the total cost of the project which previously amounted to Rp. 7,446,453,000.00 to Rp. 7,407,272,294.12. Meanwhile, in the alternative of increasing the number of workers, the total duration of the project is 94 days, from the total duration of the normal condition project for 135 days. Then there was a change in the total cost of the project which previously amounted to Rp. 7,446,453,000.00 to Rp. 7,333,584,952.22. Of the two alternatives, the most efficient alternative to accelerate work completion is to increase the number of workers.